2020
DOI: 10.1183/23120541.00362-2019
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a computer-guided consultation in the assessment of suspected obstructive sleep apnoea syndrome

Abstract: BackgroundWe describe implementation of a clinical decision support system, a computer-guided consultation (CGC), in the assessment of subjects referred with suspected obstructive sleep apnoea syndrome (OSAS).MethodsTwo cohorts of patients were assessed. The first 100 cases had data collected with the CGC by a specialist sleep physician (stage1). A further 100 cases were assessed by a nonspecialist using the CGC (stage 2). For each case, the diagnosis suggested by the CGC was compared with the final diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For example, while it is evident that the use of written personalised action plans and patient education leads to a significant reduction in healthcare utilisation, the implementation of this key practice point has been historically low, a finding mirrored here where 19% of patients were lacking a personalised action plan 19,20 . However, following CGC review, this had been achieved for nearly every patient in this cohort suggesting that the introduction of such intelligent clinical decision support system software into patient pathways may lead to a greater uptake of evidence-based practice, upskilling healthcare professionals and reducing variation in the delivery of care as has been demonstrated previously in the setting of COPD and OSA 13,14 . The CGC assesses asthma control using a multi-dimensional framework incorporating validated tools such as the of adherence and physiological indices such as lung function and its algorithms also prompt the operator to consider asthma triggers and suspected occupational factors during review.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For example, while it is evident that the use of written personalised action plans and patient education leads to a significant reduction in healthcare utilisation, the implementation of this key practice point has been historically low, a finding mirrored here where 19% of patients were lacking a personalised action plan 19,20 . However, following CGC review, this had been achieved for nearly every patient in this cohort suggesting that the introduction of such intelligent clinical decision support system software into patient pathways may lead to a greater uptake of evidence-based practice, upskilling healthcare professionals and reducing variation in the delivery of care as has been demonstrated previously in the setting of COPD and OSA 13,14 . The CGC assesses asthma control using a multi-dimensional framework incorporating validated tools such as the of adherence and physiological indices such as lung function and its algorithms also prompt the operator to consider asthma triggers and suspected occupational factors during review.…”
Section: Discussionmentioning
confidence: 71%
“…An integral part of the project is the use of technology including a bespoke audit tool to identify patients most likely to benefit from review and the introduction of clinical decision support system software in the form of a clinical guided consultation system (CGC). We have previously reported that the use of a CGC results in greater implementation of guideline-level care in both chronic obstructive pulmonary disease (COPD) and obstructive sleep apnoea (OSA) 13,14 . In this preliminary evaluation, we report the initial impact of implementing these technologies within primary care as part of the STARRS-GM project pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Similar initiatives have been trialled in other therapy areas. 27,28 Education and partnership needs to support equity of HRT treatment This study identified educational gaps related to menopause pathophysiology and knowledge of effective hormonal and non-hormonal treatments for HCPs working in both general practice and specialist clinics. This was supported by the high levels of agreement for statements 29-35 (99%, 100%, 98%, 98%, 97%, 100%, 98%, respectively).…”
Section: Development and Implementation Of Local Hrt Treatment Guidel...mentioning
confidence: 99%